2021
DOI: 10.1021/acssuschemeng.1c03890
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Cardboard Containers as a Low Energy Source for Cellulose Nanofibrils and Their Use in Poly(l-lactide) Nanocomposites

Abstract: Cellulose nanomaterials have attracted a great deal of interest as sustainable alternatives to nonrenewable or fossil fuel-derived materials, particularly in composite applications. Cellulose nanofibrils (CNF) are most often derived from wood sources through energy-intensive and costly mechanical fibrillation processes. In this study, recycled cardboard, referred to as old corrugated cardboard (OCC), was investigated as an alternate CNF source. OCC is a recycled material that can be obtained at one-tenth the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Being a recycled material in nature, OCC-LCNFs contained a complex composition of organic and inorganic materials . Although the LCNFs derived from wood pulp were reported to contain some surface charge, OCC-LCNFs were found to have a small zeta potential of −3.83 mV in this study, indicating a low amount of surface charge.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Being a recycled material in nature, OCC-LCNFs contained a complex composition of organic and inorganic materials . Although the LCNFs derived from wood pulp were reported to contain some surface charge, OCC-LCNFs were found to have a small zeta potential of −3.83 mV in this study, indicating a low amount of surface charge.…”
Section: Resultsmentioning
confidence: 57%
“…The agglomeration phenomenon of OCC-LCNFs and huge standard deviation in the final properties of films were also reported by other research groups. Copenhaver et al (2021) reported the agglomerated morphology of OCC-LCNFs after spray drying . Kelly et al (2021) observed the huge randomness in peel strength values of OCC-derived LCNF applied as an adhesive between two paper substrates .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in e-commerce, accelerated by the COVID-19 pandemic, has generated a rising production of corrugated packaging in the US (+4% from 2019 to 2020 equivalent to 1.3 million tons). However, the packaging recycling rate, at around 90% since 2012, has declined by 3.3% between 2020 and 2019, translating into ca. 3 million tons without market allocation. , This situation has been partly aggravated by China’s severe restrictions imposed recently on the US paper waste and recycling grade imports, mainly affecting old corrugated containerboard (OCC) and mixed paper waste. Part of the remaining nonrecycled paper waste is likely to end up in landfills or be incinerated, in case repurposing alternatives to obtain value-added paper products are not implemented. The latter was explained in detail in our previous work, where we presented a process for upcycling packaging waste, specifically OCC, to obtain high-performance tissue paper in an attempt to provide a solution to the current waste generation problem. The upcycled OCC pulp developed was a fully bleached grade with improved strength and water absorbency features.…”
Section: Introductionmentioning
confidence: 99%
“…7−11 Part of the remaining nonrecycled paper waste is likely to end up in landfills or be incinerated, in case repurposing alternatives to obtain value-added paper products are not implemented. 12− 16 The latter was explained in detail in our previous work, 8 where we presented a process for upcycling packaging waste, specifically OCC, to obtain high-performance tissue paper in an attempt to provide a solution to the current waste generation problem. The upcycled OCC pulp developed was a fully bleached grade with improved strength and water absorbency features.…”
Section: ■ Introductionmentioning
confidence: 99%